Effect of acute exercise-induced fatigue on maximal rate of heart rate increase during submaximal cycling - Thomson, R. L.; Rogers, D. K.; Howe, P. R. C.; Buckley, J. D. (Research in Sports Medicine, 2016)
Different mathematical models were used to evaluate if the maximal rate of heart rate (HR) increase (rHRI) was related to reductions in exercise performance resulting from acute fatigue. Fourteen triathletes completed testing before and after a 2-h run. rHRI was assessed during 5 min of 100-W cycling and a sigmoidal (rHRIsig) and exponential (rHRIexp) model were applied. Exercise performance was assessed using a 5-min cycling time-trial. The run elicited reductions in time-trial performance (1.34 ± 0.19 to 1.25 ± 0.18 kJ · kg-1, P < 0.001), rHRIsig (2.25 ± 1.0 to 1.14 ± 0.7 beats · min-1 · s-1, P < 0.001) and rHRIexp (3.79 ± 2.07 to 1.98 ± 1.05 beats · min-1 · s-1, P = 0.001), and increased pre-exercise HR (73.0 ± 8.4 to 90.5 ± 11.4 beats · min-1, P < 0.001). Pre-post run difference in time-trial performance was related to difference in rHRIsig (r = 0.58, P = 0.04 and r = 0.75, P = 0.003) but not rHRIexp (r = -0.04, P = 0.9 and r = 0.27, P = 0.4) when controlling for differences in pre-exercise and steady-state HR. rHRIsig was reduced following acute exercise-induced fatigue, and correlated with difference in performance.